Analysis of government roles in garbage classification. Issue 4 (February 2020) - Yue, Shuya; Shi, Xiuhua
Abstract: Waste sorting management has been popular in foreign countries. China started late and has a low technical level. It is still in the development stage. This paper analyzes the theoretical problems of urban domestic waste classification management at home and abroad. Management provides a reference.